AB0408 DOES THE PRESENCE IN THE SERUM OF ANTIPHOSPHOLIPID ANTIBODIES CORRELATE WITH SPECIFIC/NON SPECIFIC CAPILLAROSCOPIC ABNORMALITIES?. (2nd June 2020) - Ferrari, G.; Paolino, S.; Sulli, A.; Pizzorni, C.; Pacini, G.; Gotelli, E.; Lercara, A.; Smith, V.; Cutolo, M.
Abstract : Background: Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by specific vascular and obstetric manifestations and by antiphospholipid antibodies (aPL) positivity [1]. To date, little is known regarding nailfold videocapillaroscopy (NVC) alterations in APS patients and in asymptomatic aPL-carriers, non-specific abnormalities being the most frequently reported [2, 3, 4]. Objectives: To retrospectively analyze NVC alterations in APS patients and in asymptomatic aPL-carriers and to correlate NCV alterations with both clinical manifestations and serum aPL profile. Methods: Thirty-five aPL positive patients having received at least one NCV investigation (mean age 47 years, range 16-81, 31 female and 4 male) were retrospectively included in the study. For each patient complete medical history was collected with a particular attention to past vascular thrombosis and pregnancy morbidity. Patients were classified as affected by APS according to the updated Sapporo classification criteria [5]. Lupus anticoagulant (LAC), IgM and IgG anti-cardiolipin antibodies (ACL) and IgM and IgG anti-Beta2 Glycoprotein 1 (anti-B2GP1) were assessed in each patient according to the recommended procedures [5]. NCV parameters were analyzed in each patient, with a particular interest to hemorrhages or nailfold bed-parallel hemosiderin deposits (" comb-like" hemorrhages) presence [2, 6]. Statistical analysis was performed by parametric and non-parametric tests. Results: Seventeen patients (mean age 49 years, range 16-81 years) were asymptomatic aPL-carriers and 18 (mean age 46 years, range 26-71 years) were affected by APS. Within APS patients, 16 had a history of vascular thrombosis and 2 had pregnancy morbidity; in 6 patients APS was secondary to other autoimmune rheumatologic conditions (3 to Systemic Lupus Erythematosus, 2 to vasculitides and 1 to Mixed Connective Tissue Disease). Among the total number of aPL-carriers and APS patients six patients showed a normal NVC pattern, 24 patients had non-specific NVC abmormalities and 5 patients had a "scleroderma-like" pattern. Interestingly, NCV microhemorrhages were significantly more frequent in APS patients than in asymptomatic aPL-carriers, both in score and in absolute ( p =0.05 and p =0.04, respectively). Particularly, in APS patients " comb-like" hemorrhages had a statistically significant higher prevalence than isolated hemorrhages ( p =0.03). Dilated capillaries score was significantly higher in APS patients than in asymptomatic aPL-carriers ( p =0.01). Not any statistically significant difference was observed regarding other capillary parameters (score of giant capillaries, loss of capillaries, or anormal shpaes, i.e. angiogenesis). Not any statistical correlation was observed between NVC parameters and different aPL profile. Conclusion: The study shows that the total number of microhemorrhages and in particular the "comb-like" subtype, are significantly the most frequent specific abnormalities in APL patients when compared to asymptomatic aPL carriers. The presence of the "scleroderma like" NVC pattern may suggest a concomitant overlap syndrome. Not any correlation was found between aPL profile and other NVC parameters. Further studies need to develop a more specific APS NVC pattern for APS patients. References: [1]Tektonidou MG, et al RMD Open 2019; 5(1); [2]Cutolo M, Elsevier 2010, pp141-143; [3]Candela M, et al.1998:444-9; [4]Aslanidis S, et al. Clin Exp Rheumatol 2011, 29:307-9; [5]Miyakis S, et al. J Thromb Haemost 2006, 4:295–306; [6]Cutolo M, et al Best Pract Res Clin Rheumatol 2008, 22:1093-108 Disclosure of Interests: Giorgia Ferrari: None declared, Sabrina Paolino: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Carmen Pizzorni: None declared, Greta Pacini: None declared, Emanuele Gotelli: None declared, Adriano Lercara: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha